2012
DOI: 10.1063/1.3697860
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of a compressible gyrofluid model for collisionless magnetic reconnection

Abstract: International audienceIon Larmor radius effects on guide field collisionless magnetic reconnection are investigated by means of numerical simulations based on a gyrofluid model for compressible plasmas. Compressibility along the magnetic field is seen to favour the distribution of ion guiding center density along the neutral line, rather than along the separatrices, unlike the electron density. On the other hand, increasing ion temperature reduces the intensity of ion guiding flow that develop in the direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 51 publications
3
50
0
Order By: Relevance
“…The utility of the adopted models, on the other hand, lies also in their relative simplicity, which makes them amenable to an analytical treatment and permits to extract leading order information about plasma phenomena. For instance, fluid models such as those derived in this manuscript, have been used to investigate main basic features of collisionless magnetic reconnection [32,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The utility of the adopted models, on the other hand, lies also in their relative simplicity, which makes them amenable to an analytical treatment and permits to extract leading order information about plasma phenomena. For instance, fluid models such as those derived in this manuscript, have been used to investigate main basic features of collisionless magnetic reconnection [32,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic reconnection in the magnetized plasma has been extensively studied by means of fluid models. [2][3][4][5][6][7][8][9] The fluid simulations of a current-driven instability revealed that the magnetic reconnection caused by electron inertia effects is accelerated by the gradient of perturbed electron pressure around the reconnection point. 2 However, plasmas in hightemperature magnetic fusion experiments and in solar corona are almost collisionless.…”
Section: Introductionmentioning
confidence: 99%
“…(150)- (151), the contour lines of the normal fields G ± will not be allowed to reconnect during the evolution of the system. This argument was used in a number of numerical investigations [91,92,[95][96][97][98] of magnetic reconnection, to explain the formation of small scale structures and the saturation of magnetic islands in a dissipationless process.…”
Section: Isothermal Two-field Model With Electron Inertiamentioning
confidence: 99%